2013
DOI: 10.1155/2013/261037
|View full text |Cite
|
Sign up to set email alerts
|

Role of Th17 Cells in Skin Inflammation of Allergic Contact Dermatits

Abstract: Extending the classical concept considering an imbalance exclusively of T helper(h) 1 and Th2 cells on the bottom of many inflammatory diseases, Th17 cells were recently described. Today, there is sufficient experimental evidence to classify psoriasis and allergic contact dermatitis (ACD) amongst other inflammatory skin disorders as IL-17 associated diseases. In several human studies, T-cell-clones could be isolated from eczema biopsies, and high IL-17 levels were observed after challenge with allergen. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 98 publications
(100 reference statements)
3
46
0
1
Order By: Relevance
“…We found in allergic inflamed ears from Mincle-KO mice a suppressed production of IL-17A, which is regarded as a signature cytokine for Th17 cells (38). Th17 cells play a crucial role as effector cells in the pathogenesis of allergic contact dermatitis, psoriasis, and autoimmune diseases (39)(40)(41). Thus, the activation of Mincle during the development of allergic contact dermatitis may lead to a bias that influences T-cell polarization.…”
Section: Discussionmentioning
confidence: 99%
“…We found in allergic inflamed ears from Mincle-KO mice a suppressed production of IL-17A, which is regarded as a signature cytokine for Th17 cells (38). Th17 cells play a crucial role as effector cells in the pathogenesis of allergic contact dermatitis, psoriasis, and autoimmune diseases (39)(40)(41). Thus, the activation of Mincle during the development of allergic contact dermatitis may lead to a bias that influences T-cell polarization.…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 is able to enhance the activation and proliferation of T cells [18], while IFN-γ is considered to stimulate macrophages [19]. In addition, the other important pro-inflammatory cytokines, such as TNF-α and IL-17a, are also involved in hypersensitivity responses [20][21][22]. Our data indicated that obaculactone could reduce the mRNA levels of IL-2, IFN-γ, TNF-α and IL-17a (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Experiments for ACD control have focused on prevention of DC migration, inhibition of Th1/Th2/Th17 responses and reduction of local inflammatory cytokine products [12,14]. Attempts to modulate the immune response to ACD have been conducted in a number of clinical trials but have achieved only limited success [15].…”
Section: Introductionmentioning
confidence: 99%